Predication in 'Alī al-Qushjī: One and Many - Mehmet Özturan (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2024)
This paper examines the relationship between the fundamental metaphysical concept of unity (waḥda) and the predication schema. The latter posits that “a categorical proposition requires the subject and predicate to be identical in one respect and distinct in another,” as treated by ‘Alī alQushjī (d. 879/1474) in the kalām commentary titled Sharḥ al-Tajrīd al-‘Aqā’id. This schema, drawn from the works of Fakhr al-Dīn al-Rāzī (d. 606/1210), was later integrated into Tajrīd al-iʿtiqād by Naṣīr al-Dīn al-Ṭūsī (d. 672/1274), and subsequently became part of the discourse in philosophical kalām texts, particularly in the commentaries on Tajrīd al-iʿtiqād. Commentaries present a variety of distinct approaches to grounding the above schema within the discussion of ḥaml (predication). Curiously, the same schema is also addressed in an entirely different context, sc., in the section on unity-multiplicity (waḥda-kathra) in Sharḥ al-Tajrid al-‘Aqa’id. In the ḥaml section, kalām scholars frequently argued that the subject term and predicate term of a categorical proposition must be unified in one respect and distinct in another. In the section on unity and multiplicity, however, it was more common for kalām scholars to posit that entities described as both ‘one’ and ‘many’ must be ‘one’ in one respect, but ‘many’ in yet another respect. In short, unity and multiplicity are addressed within two distinct contexts: one pertaining to logic and the other to metaphysics. By analyzing Qushjī’s commentary, this paper seeks to underscore the intersection between the concepts of unity and multiplicity and the metaphysical foundations of predication in categorical propositions—an area that has not yet received sustained scholarly attention. By demonstrating how logical structures are rooted in their metaphysical foundations, the paper emphasizes the importance of examining logical concepts, such as categorical propositions, alongside metaphysical concepts like unity and multiplicity.